2018
DOI: 10.1007/s11356-017-1144-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation and source apportionment of PM2.5-bound trace elements at a coastal area in southwestern Taiwan

Abstract: The aim of this study is to investigate the seasonal variations and source apportionment on atmospheric fine particulate matter (PM) mass and associated trace element concentrations at a coastal area, in Chiayi County of southwestern Taiwan. Particle measurements were conducted in 2015. Twenty-three trace elements in PM were analyzed using inductively coupled plasma mass spectrometry (ICP-MS). Multiple approaches of the enrichment factor (EF) analysis and positive matrix fraction (PMF) model were used to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The adjusted covariates varied for the different dependent variables and are detailed in the legend of Tables. More importantly, in PM concentrations we adjusted for meteorological influences including season, raining, temperature, humidity, and wind velocity based on previous studies [30,31]. The intervention effect was confirmed if the two-way interaction effect was significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adjusted covariates varied for the different dependent variables and are detailed in the legend of Tables. More importantly, in PM concentrations we adjusted for meteorological influences including season, raining, temperature, humidity, and wind velocity based on previous studies [30,31]. The intervention effect was confirmed if the two-way interaction effect was significant.…”
Section: Discussionmentioning
confidence: 99%
“…The calibration was performed before collecting the data to improve accuracy and reliability. Since PM concentrations are affected by meteorological influences, such as temperature, humidity, wind velocity, and indoor emissions, those variables were treated as confounders [30,31]. According to the 2012 Environment Protection Administration of Taiwan air quality standards [32], the daily mean or 24-h maximum of PM 10 is 125 µg/m 3 , and that of PM 2.5 is 35 µg/m 3 .…”
Section: Environment Assessmentmentioning
confidence: 99%
“…For example, Cu, Pb, Se, and As were found to be the highest inorganic elements in PM 2.5 sample collected in Mountain Tai by using ICP-MS, and these inorganic elements mainly come from coal-fired power plants (Qie et al 2018 ). With ICP-MS, 23 kinds of trace inorganic elements in PM 2.5 sample collected in south Taiwan were detected, and their concentrations in cold season were higher than those in hot season (Hwang et al 2018 ). The method detection limits were in the range 1.83 × 10 − 2 –24.3 µg L −1 for all selected trace elements.…”
Section: Detection Methods For Pm 25 Chemical Comp...mentioning
confidence: 99%
“…3). An earlier study found that emissions from steel industry was the dominant source of PM 2.5 during the cold season in Chiayi County, Taiwan (where site #6 is located) because of the high content of Ca, Ti, Pb, and Fe [46]. After investigating the metal compositions of lterable stack total suspended particles emitted from industrial activities in Taiwan, Lin et al [47] 3, Fig.…”
Section: River Dust From the Choshui River Catchmentmentioning
confidence: 99%